2021
DOI: 10.1186/s13012-021-01108-0
|View full text |Cite
|
Sign up to set email alerts
|

Implementation strategies to improve statin utilization in individuals with hypercholesterolemia: a systematic review and meta-analysis

Abstract: Background Numerous implementation strategies to improve utilization of statins in patients with hypercholesterolemia have been utilized, with varying degrees of success. The aim of this systematic review is to determine the state of evidence of implementation strategies on the uptake of statins. Methods and results This systematic review identified and categorized implementation strategies, according to the Expert Recommendations for Implementing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 107 publications
1
23
0
1
Order By: Relevance
“…Adequate medication compliance could be plausibly demonstrated with a significant reduction in cholesterol and LDL cholesterol levels in patients on statin medication relative to those without. These results are consistent with data from a meta-analysis of 86 randomized controlled trials, which also demonstrated significantly reduced LDL cholesterol, increased rates of statin prescription and improved statin adherence [13]. This study also showed improved LDL cholesterol reduction over time in studies published after 2012.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Adequate medication compliance could be plausibly demonstrated with a significant reduction in cholesterol and LDL cholesterol levels in patients on statin medication relative to those without. These results are consistent with data from a meta-analysis of 86 randomized controlled trials, which also demonstrated significantly reduced LDL cholesterol, increased rates of statin prescription and improved statin adherence [13]. This study also showed improved LDL cholesterol reduction over time in studies published after 2012.…”
Section: Discussionsupporting
confidence: 89%
“…This study also showed improved LDL cholesterol reduction over time in studies published after 2012. However, this meta-analysis did not identify a single implementation strategy or group of implementation strategies with superior impact to others [ 13 ]. In the SPACE-2 trial, 42% of all patients smoking at baseline had quit smoking after one year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some healthcare systems have implemented programs for FH identification, where computer reminders invite eligible patients, identified by FH clinical diagnostic criteria, into primary care practices [ 44 ]. While the feasibility of these interventions has been measured [ 44 ], a recent systematic review of implementation strategies specific to improving statin uptake has found that implementation strategies have not been well defined nor systematically utilized and tested in practice [ 45 ]. The current study demonstrates the potential for and use of methodologies from implementation science for improving the identification of a common, high-risk genetic condition.…”
Section: Discussionmentioning
confidence: 99%
“…), она остается далекой от оптимальной [7][8][9]. Также исследователи отмечают затруднения в поиске и внедрении универсальной стратегии максимально эффективного применения статинов в клинической практике [10].…”
Section: Introductionunclassified